Development of Operando Confocal Microprobe X-ray Fluorescence Techniques to Measure Cation Transport in PEM Fuel Cells. (3rd July 2019) - Baker, Andrew M.; Cai, Yun; Ziegelbauer, Joseph M.; Agyeman-Budu, David; Woll, Arthur; Kongkanand, Anusorn; Mukundan, Rangachary; Borup, Rod L.
Abstract : State of the art proton exchange membrane (PEM) fuel cells often use PtM (M= Co or Ni) as cathode catalysts and Ce-based additives in the membrane in order to enhance their performance and durability. During operation, however, these metals dissolve and cations transport from their initial positions, which decreases their efficacy and can cause fouling of ionomer regions, resulting in performance losses and local membrane failure. Here, we report the development of a confocal microprobe X-ray fluorescence technique to directly observe transient, µm-scale through-thickness migration of Ce 3+ cations, in operando for the first time. At 80°C and 50% RH, Ce 3+ migrates from the PEM into ionomer regions of the cathode catalyst layer (CL), saturating the CL ionomer and forming a gradient in the PEM after around 10 minutes at 100 mA cm -2 . Upon removal of load, Ce 3+ diffuses and equilibrates between ionomer regions of the CL and PEM. These results demonstrate the rapid effects of cation transport in the through-thickness direction over the range of current densities tested (50-100 mA cm -2 ).